Acute care for patients exposed to a chemical attack: protocol for an international multicentric observational study. Issue 9 (29th September 2022) - Bourassa, Stephane; Noebert, Daniel; Dauphin, Marc; Rambaud, Jerome; Kawaguchi, Atsushi; Léger, François; Beijer, Daan; Fortier, Yvan; Dligui, Mina; Ivanovski, Hristijan; Simard, Serge; Jouvet, Philippe; et al.
Abstract : Introduction: The use of weapons of mass destruction against civilian populations is of serious concern to public health authorities. Chemical weapons are of particular concern. A few studies have investigated medical responses in prehospital settings in the immediate aftermath of a chemical attack, and they were limited by the paucity of clinical data. This study aims to describe the acute management of patients exposed to a chemical attack from the incident site until their transfer to a medical facility. Methods and analysis: This international multicentric observational study addresses the period from 1970 to 2036. An online electronic case report form was created to collect data; it will be hosted on the Biomedical Telematics Laboratory Platform of the Quebec Respiratory Health Research Network. Participating medical centres and their clinicians are being asked to provide contextual and clinical information, including the use of protective equipment and decontamination capabilities for the medical evacuation of the patient from the incident site of the chemical attack to the moment of admission at the medical facility. In brief, variables are categorised as follows: (1) chemical exposure (threat); (2) prehospital and hospital/medical facility capabilities (staffing, first aid, protection, decontamination, disaster plans and medical guidelines); (3) clinical interventions before hospital admission, including the use of protection and decontamination and (4) outcomes (survivability vs mortality rates). Judgement criteria focus on decontamination drills applied to any of the patient's conditions. Ethics and dissemination: The Sainte-Justine Research Centre Ethics Committee approved this multicentric study and is acting as the main evaluating centre. Study results will be disseminated through various means, including conferences, indexed publications in medical databases and social media. Trial registration number: NCT05026645 .